Lactation and resource limitation affect stress responses, thyroid hormones, immune function, and antioxidant capacity of sea otters (Enhydra lutris). Issue 16 (25th July 2018) - Chinn, Sarah M.; Monson, Daniel H.; Tinker, M. Tim; Staedler, Michelle M.; Crocker, Daniel E.
Abstract: Lactation is the most energetically demanding stage of reproduction in female mammals. Increased energetic allocation toward current reproduction may result in fitness costs, although the mechanisms underlying these trade‐offs are not well understood. Trade‐offs during lactation may include reduced energetic allocation to cellular maintenance, immune response, and survival and may be influenced by resource limitation. As the smallest marine mammal, sea otters ( Enhydra lutris ) have the highest mass‐specific metabolic rate necessitating substantial energetic requirements for survival. To provide the increased energy needed for lactation, female sea otters significantly increase foraging effort, especially during late‐lactation. Caloric insufficiency during lactation is reflected in the high numbers of maternal deaths due to End‐Lactation Syndrome in the California subpopulation. We investigated the effects of lactation and resource limitation on maternal stress responses, metabolic regulation, immune function, and antioxidant capacity in two subspecies of wild sea otters (northern: E. l. nereis and southern: E. l. kenyoni ) within the California, Washington, and Alaska subpopulations. Lactation and resource limitation were associated with reduced glucocorticoid responses to acute capture stress. Corticosterone release was lower in lactating otters. Cortisol release was lower under resource limitation and suppression during lactation was only evident under resource limitation. Lactation and resource limitation were associated with alterations in thyroid hormones. Immune responses and total antioxidant capacity were not reduced by lactation or resource limitation. Southern sea otters exhibited higher concentrations of antioxidants, immunoglobulins, and thyroid hormones than northern sea otters. These data provide evidence for allocation trade‐offs during reproduction and in response to nutrient limitation but suggest self‐maintenance of immune function and antioxidant defenses despite energetic constraints. Income‐breeding strategists may be especially vulnerable to the consequences of stress and modulation of thyroid function when food resources are insufficient to support successful reproduction and may come at a cost to survival, and thereby influence population trends. Abstract : We examined the physiological effects of lactation on an extreme income breeder, the sea otter, and energy allocation trade‐offs between responses to stress, regulation of metabolism, immune response, and antioxidant capacity with reproduction. This study provides the first evidence for physiological mechanisms that may underlie End‐Lactation Syndrome (ELS) a significant cause of mortality for the threatened southern subspecies and for the effects of resource limitation on the most expensive life‐history stage on a species already at the edge of it energetic limits. For income‐breeding strategists, where reproductive effort is directly linked to energy acquisition during lactation, and real‐time nutrient limitation will have direct repercussions on parental investment and lactation duration, the physiological trade‐offs during lactation may affect survival of offspring, as well as survival of the female and ultimately manifest in more profound population‐level consequences.